Bilingual Class Learning Management (A Site Study at SMP Negeri 2 Purworejo) - Surti, Sri; , Prof. Dr. Budi Murtiyasa, M.Kom; , Drs. HA. Dahlan Rais, M.Hum (2013)
The purposes of this study are to describe (1) the development of instructional materials of bilingual class at SMP Negeri 2 Purworejo; (2) the bilingual learning strategies at SMP Negeri 2 Purworejo; and (3) the bilingual classroom learning interactions at SMP Negeri 2 Purworejo. It was a qualitative research using ethnography design. The main research subjects were the principal, teachers and the vice principal of curriculum affair. Data collection methods used interview, observation, and documentation. Data analysis techniques used data collection, data reduction, data display, and drawing conclusion. Data validity teachniques used triangulation. The findings suggested that (1) the development of bilingual class instructional materials created by SMP 2 Purworejo was by techniques of arranging information, scratching and translating. Teachers analyzed the materials to be developed based on the National Education Standard Board and OECD curriculums. Source of instructional materials were from domestic and foreign references as taken from Cambridge. The instructional materials developed in the form of printed and electronic. (2) Bilingual learning strategies in SMP 2 Purworejo was conducted by a semi-English approach in which teachers used bilingual language in delivering instructional material. CTL method used both in learning inside or outside the classroom. With this method, students learned to discuss and work together. Animation media was used by teachers in presenting the material. The school also increased the students 'and teachers' competence in the English language by organizing public courses. (3) Interaction of bilingual class learning at SMP 2 Purworejo was done by two-way interaction. This interaction was created because teachers made an activity of students' active learning. Teachers had planned to construct interactive learning by writing lesson plan. Students were required to answer questions, conduct discussion, and also to make a presentation using an LCD that had been prepared. The recommandation given to this research(1)In House Training should be done twice a year,(2) publish the teaching materials in the form of modules,(3) carry out English Day program,(4) apply debate method.